Reviewing the ambiguous: examining the typologies of public participation towards its evaluation - Bello, Ashiru; Dola, Kamariah; Mohd Yunus, Mohd Yazid; Maidin, Ainul Jariah; Maulan, Suhardi (Canadian Center of Science and Education, 2013)
Arguments surrounding the epistemology, as well as practical manifestation of various typologies of public participation are enormous. This highlights not only the fluid and complex nature of the concept but also how strongly tied it is to time and place. While the typology of public participation is often viewed from the perspective of engagement levels, this paper uses a dual perspective approach to discuss the various forms of participation from the perspective of both engagement levels and motives, to that of specific contextual applications. The paper also draws from the practical experiences of planners in Malaysia and Nigeria to examine the relationship between evaluation approaches for public participation and the successes of participatory processes in planning projects. The perceived contribution of participatory mechanisms to a project’s success is found to be inadequate in explaining the technique’s contribution to the overall success of planning projects. Also, the motivation of (ex-ante) evaluation is more a determinant of the project success than the focus of evaluation. There is therefore a need for coherent frameworks to integrate previous evaluation experiences in to subsequent policy guides to improve further evaluation efforts as well as planning projects.